2012
DOI: 10.1038/eye.2012.225
|View full text |Cite
|
Sign up to set email alerts
|

Which visual acuity measurements define high-quality care for patients with neovascular age-related macular degeneration treated with ranibizumab?

Abstract: Purpose The purpose of this study is to define which visual acuity (VA) measurements are the best indicators of highquality care for patients receiving intravitreal ranibizumab for neovascular age-related macular degeneration (nAMD). Methods Analysis of prospectively collected data recorded within an electronic medical record system on treatment-naive, firsteligible eyes with nAMD, treated with ranibizumab using an as-needed treatment regimen with a minimum follow-up of 1 year. Data collection included the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
3
25
0
1
Order By: Relevance
“…This completeness of data capture is made possible by routine use of an EMR,15 22 which records data conforming to a standardised dataset as a byproduct of routine clinical care. Further strengths include the reporting of incidence data and clinical characteristics over several years from a ‘real life’ medical retina service of patients actually being treated,23 rather than from population studies of disease (where patients may or may not have progressed to treatment) or from clinical trials (which have restricted inclusion criteria).…”
Section: Discussionmentioning
confidence: 99%
“…This completeness of data capture is made possible by routine use of an EMR,15 22 which records data conforming to a standardised dataset as a byproduct of routine clinical care. Further strengths include the reporting of incidence data and clinical characteristics over several years from a ‘real life’ medical retina service of patients actually being treated,23 rather than from population studies of disease (where patients may or may not have progressed to treatment) or from clinical trials (which have restricted inclusion criteria).…”
Section: Discussionmentioning
confidence: 99%
“…The CATT 6 and GEFAL 17 considered a difference of five EDTRS letters to represent noninferiority, whereas the MANTA 18 considered a difference of seven letters to be noninferior. 18 Because of the 'ceiling effect', whereby eyes starting treatment with good VA have little room for further improvement, many measures are dependent on the starting VA. 11,12,20 Adjusting for age, starting VA, number of injections, and visits reduced, but did not eliminate the significant variation between centres, suggesting there are other unmeasured factors that contribute to these variations in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In routine clinical practice the mean number of injections is B6.0 in year 1 and 3.5 in year 2. 3 In the Seven-Up study, an observation of the 4 years following on from landmark clinical studies, a mean of approximately two anti-VEGF injections per year was reported. 4 Several studies report the extent and duration of intraocular pressure (IOP) elevation following intravitreal injections and most conclude that there is an immediate pressure rise with a slow normalisation of IOP to o30 mm Hg within the subsequent 30 min.…”
Section: Introductionmentioning
confidence: 99%